Machine Intelligent Research Group MIRG Organises Student Progress Seminar - Zuriani, Mustaffa (Faculty of Computing, 2024)
The MIRG Research Group was organizing a seminar to provide a platform for students to share their views and present their progress. This activity aimed to facilitate constructive feedback from lecturers and support students in completing their studies on time (GOT).